2017
DOI: 10.1038/bjc.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based microRNAs as biomarkers for the diagnosis of colorectal cancer: a systematic review and meta-analysis

Abstract: Background:Colorectal cancer (CRC) is common and associated with significant mortality. Current screening methods for CRC lack patient compliance. microRNAs (miRNAs), identified in body fluids, are negative regulators of gene expression and are dysregulated in many cancers, including CRC. This paper summarises studies identifying blood-based miRNAs dysregulated in CRC compared with healthy controls in an attempt to evaluate their use as a screening tool for the diagnosis of CRC.Methods:A search of electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 84 publications
(206 reference statements)
0
102
0
2
Order By: Relevance
“…miRs are transcribed in the nucleus as large RNA precursors called primary microRNAs. 9 31. 6,7 While microRNAs have several normal functions related to cell growth, development and differentiation, aberrant expression of these microRNAs may contribute to tumorigenesis.…”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…miRs are transcribed in the nucleus as large RNA precursors called primary microRNAs. 9 31. 6,7 While microRNAs have several normal functions related to cell growth, development and differentiation, aberrant expression of these microRNAs may contribute to tumorigenesis.…”
Section: Micrornasmentioning
confidence: 99%
“…8 Furthermore, altered expression of microRNAs in tumor tissue or serum may have a role in the diagnosis of patients with CRC. 9 31. In addition to being grouped into positional clusters, the miR-200 family can be organized into two functional groups, based on their seed sequences; miR-200b-200-c-429 and miR-200a-141.…”
Section: Micrornasmentioning
confidence: 99%
“…
Recent years have attributed major knowledge in the research area of microRNA (miRNA), a group of short 20-22 bp nucleotides, noncoding RNAs which play key roles in many biological processes, including cancer development [6], and miRNAs have been shown to be remarkably stable in both tissue samples as well as in plasma and serum [7,8]. One reason for that is that miRNAs interact with Argonaute2, which keeps it protected from nuclease activity, therefore, making them excellent markers for blood-based detection of CRC [9][10][11].A number of studies have indeed shown that several miRNAs are of interest when aiming to detect CRC [12][13][14][15]. Kanaan et al [16] found a panel of eight circulating miRNAs (miR-532-3p, 331, -195, -17, -142-3p, -15b, -532, and -652) that could distinguish CRC from controls (AUC 0.829), Wang et al [17] identified miR-409-3p, -7, and -93 as panel that discriminated CRC from healthy persons (AUC 0.897), Wang et al [18] showed that miR-601 and
AbstractColorectal cancer (CRC) is a major cause of deaths worldwide but has a good prognosis if detected early.
…”
mentioning
confidence: 99%
“…A number of studies have indeed shown that several miRNAs are of interest when aiming to detect CRC [12][13][14][15]. Kanaan et al [16] found a panel of eight circulating miRNAs (miR-532-3p, 331, -195, -17, -142-3p, -15b, -532, and -652) that could distinguish CRC from controls (AUC 0.829), Wang et al [17] identified miR-409-3p, -7, and -93 as panel that discriminated CRC from healthy persons (AUC 0.897), Wang et al [18] showed that miR-601 and…”
mentioning
confidence: 99%
“…Today, biomarker research has been transformed by the fields of genomics, proteomics, metabolomics, and lipidomics. As a result, the possible molecular nature of a biomarker today is as varied as there are substances in the body, and includes circulating tumoral DNA (e.g., mutated EGFR gene [ 7 ] ), the various types of RNA (particularly microRNA [ 8 ] ), peptides and proteins (e.g., hormones, receptors, antibodies), [ 9 ] lipids and other metabolites, [ 10 ] circulating tumor cells, and non‐cellular vesicles called “exosomes”. [ 11 ] There are currently great expectations (e.g., [ 12–15 ] ) that these molecular and cellular biomarkers will provide the needed specificity, sensitivity, reproducibility, and cost‐effectiveness for the early diagnosis of particular types of cancer.…”
Section: Introductionmentioning
confidence: 99%